(untitled) (The Journal of the International Society of Chinese Health Practices, 2024)
A large body of evidence suggests that although Tai Chi is less effective at increasing strength, it is more effective at reducing falls among older adults than functional or muscular strength training approaches. There must be other mechanisms underlying the effects of Tai Chi in reducing falls, and we are trying to identify them. We propose the following mechanisms.1. Tai Chi’s unique movement patterns mimic fall movements and increase resistance to falls.2. As a "mind-body" exercise, Tai Chi enhances sensations, i.e., the afferent nervous system.3. Tai Chi improves the function and microstructure of the central nervous system. Substantial evidence from our research team is presented to support these mechanisms.